Single-Payer Plan for New York Could Lead the Country - Gottfried, Richard N. (American journal of public health (1971), 2018)
According to University of Massachusetts Amherst Professor of Economics Gerald Friedman, New York Health would cut $71 billion from the cost of care in New York, which he projects to be $287 billion in 2019. Health care providers spend massive amounts of time and money-more than in any industrial democracy-processing insurance company billing statements and arguing with health plans and pharmacy benefit managers, taking time away from patient care.2 (Pharmacy benefit managers consume prescriber and pharmacist time and are an increasingly costly factor in prescription pricing.) Physician practices in the United States spend four times more money and 10 times more hours interacting with payers than Canadian practices do.3 The situation is worse for smaller practices and safety net providers. [...]average Vermonters would have had to pay a much higher rate than if a progressively graduated tax had been chosen. Supporters were outspent almost six to one, and the ballot text began with the words (required by state law) "[s]hall state taxes be increased by $25 billion"-calculated to generate voter opposition, especially without any clear explanation of the cost savings the proposal would create in health care and coverage.5 The New York Health Act spells out its funding mechanism: a progressively graduated tax on income subject to the Medicare Part A tax, with the employer paying at least 80% of the tax and the tax paid in full by selfemployed individuals, and on state taxable nonpayroll income such as capital gains, interest, and dividends.